2012
DOI: 10.23939/chcht06.03.263
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and Biodeterioration of Some Natural Polymers

Abstract: This review is accumulating the information about biodamages and protection of textile materials and fibers. The contributors made a special emphasis on the problems of cotton fiber biodamaging, bast fiber biodamaging, biodamaging of artificial fibers, wool fiber biodamaging, change of structure and properties of wool fibers by microorganisms, and on the methods of textile material protection against damaging by microorganisms. The authors are also discussing the mechanism the natural polymer materials degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…S2 (a)) (Szostak‐Kotowa ; Pekhtasheva et al . ). Previously, Szostak‐Kotowa () reported that microbial growth on textiles decreases the strength, and leads to elongation, discolouration and changes in appearance.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…S2 (a)) (Szostak‐Kotowa ; Pekhtasheva et al . ). Previously, Szostak‐Kotowa () reported that microbial growth on textiles decreases the strength, and leads to elongation, discolouration and changes in appearance.…”
Section: Resultsmentioning
confidence: 97%
“…Changes in the textile colour from dark brown to black may be due to thermal degradation of the textile fibres or biological infection ( Fig. S2 (a)) (Szostak-Kotowa 2004; Pekhtasheva et al 2012). Previously, Szostak-Kotowa (2004) reported that microbial growth on textiles decreases the strength, and leads to elongation, discolouration and changes in appearance.…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric materials, such as cotton, wool and flax, provides an excellent substrate for bacteria growth because they are contaminated easily with microorganisms under the appropriate environmental conditions (Borkow & Gabbay, 2008;Gao & Cranston, 2008). Microbial proliferation eventually causes damage to the fiber materials and induces human infections (Gutarowska, Machnowski, & Kowzowicz, 2013;Pekhtasheva, Neverov, Kubica, & Zaikov, 2012;Deshmukh, Deshmukh, Zade, & Thakare, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…However, bacteria also play a significant role (Bacillus sp., Cellulomonas sp., Cellvibrio sp., Clostridium sp., Pseudomonas sp., Streptomyces sp.) [35,36] . The wool is characterised by high content of various amino acids.…”
Section: Resultsmentioning
confidence: 99%